Problems and challenges of the transfer of social food programs to fight poverty - Caballero Martín, Víctor (2004)
The social programs to combat poverty have been under permanent observation both by the beneficiaries of these programs and by the criticism they received for the political use that was given to them. Two major issues aroused interest in the study of these programs. First, because, despite the investment from the public treasury and the contributions from international cooperation for the strategy to combat poverty, the problems that persisted showed the poor focus of the investment, the loss of objectives, the leaking of aid and the dispersion of the programs, in addition to the serious problems of administration of the resources. Second, because reelectionist political campaigns were associated with the intensification and expansion of food support for urban and rural populations.